Regulation of Notch signaling and endocytosis by the Lgl neoplastic tumor suppressor. - Portela, M.; Parsons, L.M.; Grzeschik, N.A.; Richardson, H.E. (Cell Cycle, 2015)
The evolutionarily conserved neoplastic tumor suppressor protein, Lethal (2) giant larvae (Lgl), plays roles in cell polarity and tissue growth via regulation of the Hippo pathway. In our recent study, we showed that in the developing Drosophila eye epithelium, depletion of Lgl leads to increased ligand-dependent Notch signaling. lgl mutant tissue also exhibits an accumulation of early endosomes, recycling endosomes, early-multivesicular body markers and acidic vesicles. We showed that elevated Notch signaling in lgl(-) tissue can be rescued by feeding larvae the vesicle de-acidifying drug chloroquine, revealing that Lgl attenuates Notch signaling by limiting vesicle acidification. Strikingly, chloroquine also rescued the lgl(-) overgrowth phenotype, suggesting that the Hippo pathway defects were also rescued. In this extraview, we provide additional data on the regulation of Notch signaling and endocytosis by Lgl, and discuss possible mechanisms by which Lgl depletion contributes to signaling pathway defects and tumorigenesis.